FAKTOR-FAKTOR PENOLAKAN TANZANIA TERHADAP KERJASAMA ECONOMIC PARTNERSHIP AGREEMENT (EPA) DENGAN UNI EROPA - Wasia, Zuriel Juliando; Dewi, Putu Ratih Kumala; Parameswari, A.A. Agung Ayu Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
A BS TRACT   The EPA Cooperation between EAC and European Union has been conducted for over than 10 years. The cooperation reached its full agreement in 2014 and is planned to be signed in 2016. EPA is a free trade cooperation to remove obstacles such as tariffs. But at the time of signing, Tanzania as one of the members of EAC, refused to sign the EPA cooperation. Tanzania considers the EPA not to have a positive impact on its domestic condition. Tanzania wants to focus and build on the domestic economy, and if it signs the EPA it will make the aims and interests disturbed. This study aims to illustrate the domestic factors affecting Tanzania's foreign policy. This study is using the concept of determinants of foreign policy through domestic factor and external environment. The focus of this study is from 2014 to 2016.   Keywords : foreign policy decision, domestic factor, external environment, EPA EAC-EU